Utility and cost‐effectiveness of molecular testing in thyroid nodules with indeterminate cytology. (3rd June 2016) - Labourier, Emmanuel
Summary: Context: Molecular testing on biopsies from thyroid nodules with indeterminate cytology can improve patient management by preventing unnecessary surgeries on benign nodules. Objective: The aim of the study was to determine the health outcome benefits and cost‐effectiveness of molecular testing in nodules with AUS/FLUS or FN/SFN cytology. Design: The initial diagnosis and treatment of a hypothetical cohort of adult U.S. patients with solitary thyroid nodules ≥1 cm was simulated by decision analytic modelling using Medicare cost estimates for three management strategies, standard of care without molecular testing (StC), gene expression classifier (GEC) and mutation and miRNA testing (MMT). Results: Gene expression classifier decreased the rate of unnecessary surgeries by 32% relative to StC, yielding incremental costs of 1008 per patient or 5070 per unnecessary surgery avoided. MMT decreased the surgery rate by 67%, yielding incremental savings of −1384 per patient or −3170 per unnecessary surgery avoided. Results remained robust in deterministic sensitivity analyses; MMT was dominant for every variable tested. Independent of cancer prevalence, MMT yielded 52% fewer unnecessary surgeries relative to GEC #bib70% fewer two‐stage thyroidectomies and correctly identified 70% more benign nodules. Test specificity had to be >68% for molecular testing to be cost‐effective and decrease by >50% the rate of unnecessary surgeries performed on benign nodules. Conclusions: Molecular testing with high benign diagnostic yield can generate both positive health outcomes (less surgeries) and positive economic outputs (cost savings). These results are consistent with previously reported cost‐utility data and provide valuable insights for informed decision‐making by patients, physicians and payers.